Seed viability changes during fruit ripening of Tapirira guianensis Aubl.: Implications for collection (Research, Society and Development, 2020)
Environmental changes provoked by man have caused great impacts on nature with irreparable consequences to the environment, life, and biodiversity. Species as Tapirira guianensis that have high ecological potential, due to adaptability, fast growth, and abundant fruit production, can contribute to the restoration of these environments. The objective of this work was to verify the influence of the fruit maturation stage on the physiological potential of the Tapirira guianensis seeds from three genitor plants and, thus, to define seed collection patterns based on the fruit external characteristics. The experiment was performed in a completely randomized design, in factorial scheme 3 x 3, three parent trees (1, 2, and 3) and three fruit maturation stages (green, intermediate and mature fruits), containing 4 replicates of 25 seeds per treatment. Seeds from mature fruits in comparison to those of green fruits presented significant reductions in the water content in the parent trees 1, 2 e 3 de 11%, 21%, and 28%, respectively. Otherwise, seeds from mature fruits presented significant increases in the emergence and emergence speed index of 7% and 11% for parent tree 1, 76%, and 108% for parent tree 2, and 40% and 40% for parent tree 3, in comparison to the seeds from green fruits. This research revealed that was possible to define physiological maturation of seeds according to the fruit maturation stages, being the seeds from intermediate and mature fruits that present higher germination power and development of seedlings and, therefore, indicated for collection of Tapirira guianensis seeds.